Peran Kepemimpinan Perempuan dalam Pengembangan Mutu Madrasah: Studi Kasus di Madrasah Aliyah Muhammadiyah Belang Kabupaten Minahasa Tenggara - Rahayu Bayahi; T D E Abeng; Lies Kryati (The Center for Gender and Children Studies, the Institute for Research and Communing Service, State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2021)
This study examines the Role of Women's Leadership in Madrasah Quality Development (Case Study at Madrasah Aliyah Muhammadiyah Belang Southeast Minahasa). The purpose of this study is to determine the planning program in quality development. This study uses qualitative research, namely in collecting data used observation, interviews and documentation. The location of this research is Madrasah Aliyah Muhammadiyah Belang with the research subject being the Head of Madrasah, Deputy Head of Madrasah, Administrative Staff as well as teachers and students. This study indicates that: (1) The Head of Madrasah Aliyah Muhammadiyah Belang has been maximal in carrying out her duties as a female leader or head of Madrasah in establishing good communication with all educators, staff or all students in the madrasa. The head of the madrasa also has an assertive nature so that she is not underestimated by his subordinates, this assertive nature makes one of his characteristics that is feared by students and teachers. (2) The Head of Madrasah involves many people in planning the programs that have been implemented. The head of the madrasa is also very enthusiastic in carrying it out so that the activities that have been carried out have gotten good results as long as she is the Head of Madrasah Aliyah Muhammadiyah Belang. (3) The head of the Madrasah who provides opportunities for teachers, especially those with a bachelor's degree, to attend training or workshop. Some teachers already have a bachelor's degree and are certified. (4) Then the reality on the ground is that the condition of the facilities and infrastructure in the madrasa is not sufficient when compared to the number and needs of students Abstrak Penelitian ini adalah tentang Peran Kepemimpinan Perempuan Dalam Pengembangan Mutu Madrasah (Studi Kasus di Madrasah Aliyah Muhammadiyah Belang Minahasa Tenggara). Tujuan dari penelitian adalah untuk mengetahui program perencanaan dalam pengembangan mutu. Penelitian ini menggunakan penelitian kualitatif yaitu dengan pengumpulan data yang digunakan seperti pedoman observasi, wawancara dan dokumentasi. Lokasi penelitian adalah Madrasah Aliyah Muhammadiyah Belang dengan subjek penelitian Kepala Madrasah, Wakil Kepala Madrasah, Bagian Tata Usaha sekaligus sebagai guru dan juga siswa. Hasil penelitian menunjukan bahwa: (1) Kepala Madrasah Aliyah Muhammadiyah Belang sudah maksimal dalam menjalankan tugasnya sebagai seorang pemimpin perempuan atau kepala Madrasah dalam memotivasi menjalin komunikasi yang baik dengan seluruh tenaga pendidik, staf ataupun seluruh peserta didik yang ada di madrasah. Kepala madrasah juga memiliki sifat tegas agar supaya tidak di anggap remeh oleh bawahan, sifat tegas ini menjadikan salah satu sifat khas beliau yang ditakuti siswa maupun guru. (2) Kepala Madrasah melibatkan banyak orang dalam perencanaan program-program yang telah terlaksanakan. Kepala Madrasah juga sangat antusias dalam menjalankannya sehingga kegiatan yang telah terlaksanakan mendapatkan hasil yang baik selama beliau menjadi kepala madrasah di Madrasah Aliyah Muhammadiyah Belang. (3) Kepala Madrasah yang memberikan peluang bagi guru-guru khususnya bergelar S1 untuk mengikuti pelatihan atau diklat. Beberapa guru sudah memiliki ijasah S1 dan bersertifikasi. Kemudian kenyataan di lapangan bahwa kondisi sarana dan prasarana yang ada di madrasah cukup baik. (4) sarana dan prasarana belum mencukupi bila dibandingkan dengan jumlah dan kebutuhan peserta didik.